Bonding and stoichiometry in low-energy radio frequency magnetron sputtered ZnO thin films on flexible substrate. (January 2021) - Iheomamere, Chukwudi E.; Arnold, Corey L.; Rathod, Urmilaben P.; Omotosho, Khalil D.; Voevodin, Andrey A.; Shepherd, Nigel D.
Abstract: Spectroscopic and electrical studies of ZnO thin films grown by radio frequency magnetron sputtering at low power without substrate heating revealed improved stoichiometry and reduced free carrier concentration with increasingly energetic growth conditions, which is opposite to what is typically observed. Hall measurements showed a decrease in carrier concentration from 6.9 × 10 19 cm −3 to 1.4 × 10 19 cm −3 as power increased from 40 W to 120 W, and a decrease in carrier concentration from 8.6 × 10 19 cm −3 to 2.6 × 10 19 cm −3 as the deposition pressure decreased from 1.2 to 0.4 Pa. These findings correlated well with XRD, x-ray photoelectron spectroscopy and photoluminescence results, which showed that more energetic conditions increased the fraction of oxygen that was stoichiometrically bonded. The change in the absorption edge, likely due to a Burstein-Moss shift, was also in qualitative agreement. In the range of conditions used, energy transfer from the plasma to the growing film governs bonding, stoichiometry and hexagonal nanocrystalline film formation and growth. Highlights: Conductive, transparent ZnO can be obtained at low power without substrate heating. More energetic processing improved stoichiometry and decreased carrier concentration. Burstein-Moss shift observed. Atomic peening and energy transfer from the plasma are necessary supplies of energy for bonding and film formation.